La santé mentale des étudiants : mieux prendre la mesure et considérer les enjeux - Morvan, Y.; Frajerman, A. (L'Encéphale, 2021)
Résumé La santé mentale représente un coût élevé pour la société pourtant la prévention semble efficace et rentable. Toutefois plusieurs problèmes se posent concernant la mesure en santé mentale et notamment de définir ce que l’on entend par pathologie. Il convient également de comprendre comment les mesures de ces concepts sont opérationnalisées et comment les outils sont construits. Ainsi pour la dépression, il existe de nombreuses échelles différentes qui ne prennent pas en compte les mêmes symptômes et pour une même échelle le seuil et la période de temps étudiés peuvent varier, ce qui a des conséquences sur les données de prévalence obtenues. Il est également important de s’interroger sur les hypothèses et modèles utilisés concernant les causes des pathologies psychiques qui sous-tendent les outils et les recherches réalisées. Pour finir, les troubles mentaux, tels que définis actuellement, débutent majoritairement avant l’âge de 24 ans pour trois quarts des personnes. Les étudiants, dont l’âge est majoritairement compris en 18 et 25 ans, sont une population particulièrement à risque ce qui peut avoir des conséquences très importantes tant individuelles que sociales. Les conséquences du coronavirus et du confinement, en lui-même et en raison de ses conséquences économiques et sociales, pourraient avoir un impact délétère sur leur santé mentale. Malheureusement, il existe encore peu de données sur les étudiants français et les études existantes ne sont pas facilement comparables en raison de méthodologies différentes. Tous ces éléments plaident pour la mise en place d’une politique d’évaluation de la santé mentale des étudiants. Mental health represents a high cost for society, estimated at 109 billion euros per year in France, 80 % of which are indirect costs. Mental diseases start before the age of 24 for 75 % of patients. Students, whose age is predominantly between 18 and 25, are a particularly high-risk population and for whom mental illness can have very serious consequences. The Observatoire de la vie Etudiante surveys from 2016 found a 12 month prevalence of depression of 15 % with suicidal thoughts in 8 % of the students higher than what is observed in the French general population, respectively 10 % and 5 %. The confinement itself and its consequences both economic (unemployment, difficulty for young people to find a job…) and social (isolation) could have a very bad effect on their mental health. The survey made by a governmental organization (Santé Publique France) revealed a significant increase in the prevalence of anxiety disorders at the start of confinement in the general population. This prevalence decreased during confinement but remained significantly higher than in 2017. Economic simulated data indicate that prevention in mental health could not only be effective but also profitable. In France, reimbursement by national health insurance of 12 sessions of psychologists for young people (between 11 to 21) is being tested in order to further and widely implement psychological prevention strategies rather than relying on already widely reimbursed pharmacological treatments. There are, however, several issues to discuss. First of all, is the need to define what psychopathology is considered to be. Then, it should be understood how measures of these concepts are created, how tools are constructed and how they operate in their environment. For depression, many different scales exist and even if the most used one are taken into account, they have very little content or symptoms in common. In addition, for the same scale, many different cut-offs exist to define whether a case should be considered as pathological or not, and so it is with the period of time studied being considered that may vary, both leading to consequences such as the differences observed in prevalence. Other biases should also be considered such as the age of the participants, the gender, the size of the sample, the response rate, the method of assessment and recruitment. Finally, it is necessary to question the assumptions and models used concerning the causes of psychic pathologies. Biological hypotheses on the origin of depression involve genetics and inflammation, but sociological and psychological factors must also be considered as well as the underlying complexity both in their nature and interactions at different structural levels of space and time. We should avoid drifting towards a biological or a sociological reductionism and move forward through complex systems approaches and models. With regard to student mental health in France, unfortunately, quality data are still lacking, and existing studies are difficult to compare as some may also have methodological issues. This article leads to the conclusion that there is a need for policies to assess student mental health at both local and national levels with a reflexional thinking on the tools and scales to use as measurements of these phenomena. This approach does not require being too assertive, but should have full transparency on the way the measures were designed and obtained. Measures are as much needed as are the needs for coordinated prevention and care in mental health.
Keywords: Depression; Dépression; Etudiants; Measures; Mental health; Mesures; Methodology; Méthodologie; Santé mentale; Students